2015
DOI: 10.17707/agricultforest.61.2.05
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plantlets Density and Growth Mediacomposition on Potato Mini-Tuber Production in Hydroponic Sand Culture

Abstract: SUMMARYHydroponic Sand Culture (HSC) is a relatively low cost method for potato minituber production. Intensive production under HSC requires applying appropriate growth media composition and plantlet density. An experiment was conducted under HSC in a controlled greenhouse to evaluate growth media composition and plantlet density effect on potato micropropagated plantlets growth, tuberization and concentration of petiole phosphorus and leaf nitrogen. A factorial experiment based on randomized complete block d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This finding is possibly due to this trait being controlled by genetic rather than environmental factors. Similarly, Akassa et al (2014) and Darvishi et al (2015) also found that the specific gravity of tubers was not affected by plant density. Good-quality potatoes should have a specific gravity of > 1.08 g m -3 , with values of < 1.07 g m -3 generally being considered unacceptable for processing (Kabira & Lemaga, 2006).…”
Section: Discussionmentioning
confidence: 81%
“…This finding is possibly due to this trait being controlled by genetic rather than environmental factors. Similarly, Akassa et al (2014) and Darvishi et al (2015) also found that the specific gravity of tubers was not affected by plant density. Good-quality potatoes should have a specific gravity of > 1.08 g m -3 , with values of < 1.07 g m -3 generally being considered unacceptable for processing (Kabira & Lemaga, 2006).…”
Section: Discussionmentioning
confidence: 81%